Putting Climate Information into Farmers' Hands - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (https://ccafs.cgiar.org) is working with farmers from Kaffrine, Senegal, on how to communicate and package climate forecasts. The project is rolled out together with the National Meteorological Agency (ANACIM), the National Agency for Agricultural and Rural Advice (ANCAR); the Ministry of Agriculture; Senegal Department of Rural Development (SDDR), the Senegalese Agricultural Research Institute (ISRA), the International Research Institute for Climate and Society (IRI) and World Vision. Learn more: www.ccafs.cgiar.org